KEAMPUHAN AYAT AL-QUR’AN SEBAGAI SARANA PENGUSIR SETAN (ANALISIS BUKU SENJATA SPRITUAL SANTRI) - Muhammad Shulhi Alhadi Siregar (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2018)
This paper attempts to examine how the process of transmitting and transforming the Qur'an in the book "The Spritual Weapon of Santri" which became a recommended practice for the santri. Because in this book the author tries to collect or write a deed-quoted from the Qur'an and hadith. But on the other hand the author tries to focus on the part about how a practice can fortify itself from temptation and satanic disorder and because the most dominant of the deeds is the verses of the Qur'an, it will be the study of Living Qur'an. How the verses of the Qur'an are only limited to the message that Allah sent to the Prophet Muhammad, became a daily deeds that can be used to guard against the disturbances of supernatural beings.